Swarming caterpillar: a resurrecting pest in rice ecosystem - Pandi, Guru Pirasanna; Adak, G. Totan; Jena, Mayabini (Indian Farming, 2018)
Swarming caterpillar earlier considered as a sporadic pest and cause substantial damage to the crops in southern part of the Indian contingent, but since 2000, in the eastern and north-eastern part of the country its outbreak has occurred in five times. In the context of changing climatic scenario this pest are need to monitored on time otherwise it may hamper the rice yield.